Een crisis die mogelijkheden biedt - Socoloff, Ivana Claudia (2015)
The aim of this article is to briefly show how certain values associated with specific territories enter the international circuits of financial capital, by depicting the process of urban renewal in the area of Abasto (Buenos Aires, Argentina). In doing so, we will describe how the urban plans of a social organization going through an economic crisis became an "opportunity" to be appropriated by transnational financial capital. In this sense, like other pieces in this issue of AGORA, the article is part of a series of reflections seeking to trace the interdependencies between finance and real estate, based on concrete cases. To do this, we first describe the process of urban renewal in the Abasto area as a typical case of renovation seeking to boost land values. Then, we show how the appropriated land values entered transnational circuits, through what we term a "financial alchemy" designed to make this possible. Finally, we will conclude with some briefs remarks on the role of the crisis as an "opportunity" for transforming the city, and its limits.